Assessing and Comparing of Balance and Flexibility Among Elderly Men and Women in the Age Group of 60-79 Years - Vahid Valipour Dehnou; Reza Motamedi (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Functional fitness is a concept that reflects an older adult’s ability to perform physical activities of daily living with relative ease. The aim of the present study is to assess and compare balance and flexibility in elderly men and women in the age group of 60-79 years in Khorramabad.  Methods & Materials In this descriptive and comparative study, 140 elderly people (35 males and 35 females aged 60 to 69 years and 35 males and 35 females aged 70 to 79 years) were conveniently selected and voluntarily participated. To examine balance and flexibility, functional reach and sit and reach tests were used, respectively. For ease of use, tests were performed at the subjects’ residence. Independent samples t-test was used to identify any significant difference, and statistical significance was set at p<0.05.  Results Results showed that significant differences were observed between balance and flexibility of males aged 60 to 69 years and 70 to 79 years (P<0.05); significant differences were observed between balance and flexibility of females aged 60 to 69 years and 70 to 79 years (P<0.05); significant differences were observed between balance and flexibility of males and females aged 60 to 69 years and 70 to 79 years (P<0.05) and 69 to 79 years. Balance and flexibility of both males and females decreased progressively, and the rate of decrement was greater in females than males (-15.79% vs. -14.55% for balance and -17.79% vs. -12.63% for flexibility). Conclusion Given the significant role of balance and flexibility in the better performance of daily activities and the reducing them in elderly men and women, it is important to reinforce these two factors of physical fitness throughout life. And to reinforce them, a multicomponent exercise intervention could be the best option.